Erysipelas in a 10-month-old boy with atopic dermatitis. - Ben Salem, S.; Daflaoui, H.; Almheirat, Y.; Dikhaye, S.; Zizi, N. (European Journal of Pediatric Dermatology, 2023)
Erysipelas is an infrequent infection of the skin and subcutaneous tissue that mainly affects adults. It is classically caused by a group A beta-hemolytic Streptococcus. The most frequent sites are the lower limbs and the face, on which a well-defined, warm, erythematous and indurated plaque is evident. The case of a 10-month-old infant previously affected by atopic dermatitis was described.